2009
DOI: 10.2118/109915-pa
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Transport and Sorption Behavior in Confined Coal Cores for Carbon Sequestration

Abstract: Measurements of sorption isotherms and transport properties of carbon dioxide (CO 2 ) in coal cores are important for designing enhanced coalbed-methane/CO 2 -sequestration field projects. Sorption isotherms measured in the laboratory can provide the upper limit on the amount of CO 2 that might be sorbed in these projects.Because sequestration sites will most likely be in unmineable coals, many of the coals will be deep and under considerable lithostatic and hydrostatic pressures. These lithostatic pressures m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The interplay of these factors likely contributes to the complex response observed during CO 2 uptake and redistribution within coal. 24,99 The dynamic response observed here in terms of extraction and transport of organic compounds from the coal matrix underscores the need to resolve the cumulative (or net) effect of these factors in order to ascertain hydrocarbon fate and transport during supercritical CO 2 injection and storage in coal beds.…”
Section: ■ Discussionmentioning
confidence: 94%
“…The interplay of these factors likely contributes to the complex response observed during CO 2 uptake and redistribution within coal. 24,99 The dynamic response observed here in terms of extraction and transport of organic compounds from the coal matrix underscores the need to resolve the cumulative (or net) effect of these factors in order to ascertain hydrocarbon fate and transport during supercritical CO 2 injection and storage in coal beds.…”
Section: ■ Discussionmentioning
confidence: 94%
“…Adsorption kinetics may also be determined for various gases (e.g. for CO 2 and CH 4 ) using confining cells to apply desired pressures and temperatures (Charrière et al, 2010) and using X-ray CT methods to determine the resulting sorption isotherms (Jikich et al, 2009). These experiments have focused on the isotropic characteristics of intact or powdered coals.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Day et al, 2008Day et al, , 2010Day et al, , 2011Day et al, , 2012Durucan and Shi, 2009;Majewska and Ziętek, 2007;van Bergen et al, 2009). However, so far, there have been only a limited number of experimental studies on the sorption of gas by constrained coal (Czapliński et al, 1986;Hol et al, 2011;Jikich et al, 2009;Pone et al, 2009a,b;Ranjith et al, 2010;Wang et al, 2010Wang et al, , 2011. Czapliński et al (1986) investigated changes in strains and stresses induced in a coal sample subjected to sorption/desorption of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have reported the possible influence of stress on the adsorption of CO 2 by coal (Hile, 2006;Hol et al, 2011;Jikich et al, 2009;Pone et al, 2009a,b). Jikich et al (2009) studied apparent sorption and diffusion of gas in a coal core under a confining pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation